PROGRAM BERKELANJUTAN KELOMPOK MASYARAKAT DESA SERUT UNTUK TUMBUH KEMBANG MELALUI PELATIHAN PEMBUATAN SABUN - Mathilda Sri Lestari; Rahmatul Ahya; Darsini Suprapto (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
Community service was carried out in Serut Nguter Sukoharjo with the target audience being mothers of PKK members, with the title Sustainable Programme for Serut Village Community Groups for Growth and Development through Soap Making Training. As many as 65% of PKK members work as housewives and as farmers, so there is a lot of free time because working as a farmer is temporary or seasonal. With the training in making laundry soap, it’s hoped that it can help the family economy, besides that it is an opportunity to open an entrepreneurship by producing soap for sale. The method is carried out through 2 stages, namely the introduction stage of the ingredients for making soap and their benefits, and the soap-making training stage. The result of this training is that out of 21 participants who participated in the training, 85% of the participants were able to make soap independently.